Teaching Kazakh Folklore in the Context of Modern Literary Education of Secondary School Pupils (Journal of Educational Sciences, 2025)
The study of works of oral folk art in literature lessons as a necessary stage of literary education of school pupils requires a rethinking of the content of educational material and teaching techniques, taking into account current tasks in education.  The purpose of the article is to determine the theoretical foundations and methods of studying Kazakh folklore by genres in the literature class of V-VIII grades based on the implementation of new information and educational tasks of schoolchildren and the formation of their spiritual wealth. A teaching methodology providing gradual, complex mastering of oral folklore genres in V-VIII grades of Kazakh literature by schoolchildren is developed.A teaching method has been developed that provides for the step-by-step and comprehensive development of oral folklore genres in grades 5-8 of secondary school during Kazakh literature lessons.The literature review examines the didactic and methodological principles of teaching Kazakh literature: sequence, from simple to complex, and practice-oriented approach. The teaching methods for grades 5-6 include works of Kazakh oral folklore: fairy tales, proverbs, sayings, riddles, and myths. The first works that students in grades 5-6 become familiar with are Kazakh fairy tales. The purpose of teaching Kazakh folklore in grades 7-8 is to introduce students to the origins of the national culture of the people, enrich their spiritual world, moral ideas, aesthetic needs, and develop artistic taste, creative imagination, oral and written speech. Experimental work was conducted at school No. ____ in Almaty. ____ schoolchildren took part in the experiment to test and implement the teaching methodology. Key words: proverbs, epic, fairy tales, genres, sayings, riddles, methods of teaching language and literature.